Site-Directed Mutagenesis of HIV-1 vpu Gene Demonstrates Two Clusters of Replication-Defective Mutants with Distinct Ability to Down-Modulate Cell Surface CD4 and Tetherin - Nomaguchi, Masako; Doi, Naoya; Fujiwara, Sachi; Fujita, Mikako; Adachi, Akio (Frontiers in Microbiology, 2010)
HIV-1 Vpu acts positively on viral infectivity by mediating CD4 degradation in endoplasmic reticulum and enhances virion release by counteracting a virion release restriction factor, tetherin. In order to define the impact of Vpu activity on HIV-1 replication, we have generated a series of site-specific proviral vpu mutants. Of fifteen mutants examined, seven exhibited a replication-defect similar to that of a vpu-deletion mutant in a lymphocyte cell line H9. These mutations clustered in narrow regions within transmembrane domain (TMD) and cytoplasmic domain (CTD). Replication-defective mutants displayed the reduced ability to enhance virion release from a monolayer cell line HEp2 without exception. Upon transfection with Vpu expression vectors, neither TMD mutants nor CTD mutants blocked CD4 expression at the cell surface in another monolayer cell line MAGI. While TMD mutants were unable to down-modulate cell surface tetherin in HEp2 cells, CTD mutants did quite efficiently. Confocal microscopy analysis revealed the difference of intracellular localization between TMD and CTD mutants. In total, replication capability of HIV-1 carrying vpu mutations correlates well with the ability of Vpu to enhance virion release and to impede the cell surface expression of CD4 but not with the ability to down-modulate cell surface tetherin. Our results here suggest that efficient viral replication requires not only down-regulation of cell surface tetherin but also its degradation.